2015
DOI: 10.1097/prs.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Conflict

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Autologous tissue transfer with either pedicled or free flaps has remained the pillar of treatment for definitive reconstruction in recent conflicts. Sabino et al [ 18 ] reported 10 years of experiences at Walter Reed National Military Medical Center where 359 flaps were performed for war-related extremity trauma (143 free and 216 pedicled flaps), including poly-extremity trauma and reconstruction, with outcomes comparable to other military and civilian lower extremity reconstruction. In this series, 55 % of flaps were muscle flaps, and 42 % were fasciocutaneous flaps.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Autologous tissue transfer with either pedicled or free flaps has remained the pillar of treatment for definitive reconstruction in recent conflicts. Sabino et al [ 18 ] reported 10 years of experiences at Walter Reed National Military Medical Center where 359 flaps were performed for war-related extremity trauma (143 free and 216 pedicled flaps), including poly-extremity trauma and reconstruction, with outcomes comparable to other military and civilian lower extremity reconstruction. In this series, 55 % of flaps were muscle flaps, and 42 % were fasciocutaneous flaps.…”
Section: Reviewmentioning
confidence: 99%
“…Flap failure, hematoma, chronic pain, non-union, osteomyelitis, heterotopic ossification, and delayed amputation represent the major complications reported in war-related extremity reconstructions [ 5 , 18 ]. Overall, the success rate for flap coverage exceeds 90 % [ 2 4 , 18 ]. Sabino et al [ 18 ] reported flap failure leading to amputation in only four out of 359 cases of flap coverage (1 %).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4 Skin and soft tissue losses are especially challenging in patients with multiple extremity and/or amputee injuries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Regenerative modalities offer novel options for complicated reconstructions. 24 Herein, our case report outlines the first military nonburn-related trauma patient treated by a combination of a dermal regenerate template (DRT) followed by application of spray skin and 6:1 meshed skin grafts to address a more than 600-cm 2 abdominal skin and soft tissue deficit.…”
mentioning
confidence: 99%